The Toxoplasma pseudokinase ROP5 forms complexes with ROP18 and ROP17 kinases that synergize to control acute virulence in mice - Etheridge, Ronald D. (2014)
Polymorphic rhoptry secreted kinases (ROPs) are essential virulence factors of Toxoplasma gondii. In particular, the pseudokinase ROP5 is the major determinant of acute virulence in mice, but the underlying mechanisms are unclear. We developed a tandem affinity protein tagging and purification approach in T. gondii and used it to show that ROP5 complexes with the active kinases ROP18 and ROP17. Biochemical analyses indicates that ROP18 and ROP17 have evolved to target adjacent and essential threonine residues in switch region I of immunity related GTPases (IRGs), a family of host defense molecules that function to control of intracellular pathogens. The combined activities of ROP17 and ROP18 contribute to avoidance of IRG recruitment to the intracellular T. gondii containing vacuole, thus protecting the parasite from clearance in interferon-activated macrophages. These studies reveal an intricate, multi-layered parasite survival strategy involving pseudokinases that regulate multiple active kinase complexes to synergistically thwart innate immunity.